Implementation of Consumer Legal Protection Against Pillages of Hajj/Umrah - Ida Rosida (Journal of Social Research, 2023)
Consumer protection is crucial in ensuring the fulfillment of consumer rights, especially as the modern economy expands, leading to increased needs in daily life. Intense competition among businesses can result in some consumers falling victim to fraudulent practices. A notable example is the growing number of travel agencies organizing Umrah pilgrimages, some of which engage in unlawful activities, causing significant losses for prospective pilgrims. The introduction of Regulation No. 8 of 2018 by the Minister of Religion has established a solid foundation for safeguarding Umrah pilgrims' interests. This regulation covers essential aspects such as health protection, life insurance guarantees, incident management, and the handling of missing pilgrim documents during the pilgrimage journey. It has significantly improved the protection offered to Umrah pilgrims. To further enhance consumer protection, it is advisable for the government to reevaluate its policies regarding the organization of the Hajj/Umrah pilgrimage. Specifically, there should be a thorough examination of the separation of roles between regulators and operators in this sector. Such separation would help ensure transparency, fair practices, and a higher level of accountability, thereby enhancing the overall protection of consumers' rights and interests.